Bicyclic peptides as a new modality for imaging and targeting of proteins overexpressed by tumors - Eder, Matthias; Haberkorn, Uwe; Kopka, Klaus (Cancer research, 2019)
Molecular imaging of cancers using probes specific for tumor-associated target proteins offers a powerful solution for providing information regarding selection of targeted therapy, patient stratification, and response to therapy. Here we demonstrate the power of bicyclic peptides as targeting probes, exemplified with the tumor-overexpressed matrix metalloproteinase MT1-MMP as a target. A bicyclic peptide with subnanomolar affinity towards MT1-MMP was identified, and its radioconjugate showed selective tumor uptake in an HT1080 xenograft mouse model. Proteolytic stabilization of the peptide by chemical modification significantly enhanced the in vivo tumor signal [from 2.5%ID/g to 12%ID/g at 1 hour post injection (p.i.)]. Studies using mouse xenograft models with different cell lines show a robust correlation between tumor signals and in vivo MT1-MMP expression levels. Fatty acid modification of the bicyclic peptide extended its circulating half-life, resulting in increased tumor signals (36%ID/g at 6 hours p.i.). Comparative work with an equipotent radiolabeled MT1-MMP targeting antibody demonstrated starkly differential biodistribution and tumor accumulation properties, with the tumor signal slowly increasing to 6.2%ID/g within 48 hours. The rapid tumor penetration characteristics of bicyclic peptides, coupled with high potency and chemical versatility, thus offer high-contrast imaging probes for clinical diagnostics with compelling additional potential in targeted therapy.Significance: This work demonstrates the potential of bicyclic peptides as a platform for the development of high-contrast imaging probes for potential use in clinical cancer diagnostics and molecularly targeted therapeutics.